Effects of Production Factors on Shrimp Culture in Boushehr, Iran - Faizbakhsh, Reza (2006)
Shrimp culture in Iran is a rather new industry. It began with feasibility studies in 1989 and the shrimp farms started production in 1992. Shrimp culture is important to the four southern provinces of Iran since it is a major source of employment and a factor in the local economies. A study has been done on the economics of the shrimp culture sector in Iran and data collected from 1999 to 2001.